Transgenic mice with an R342X mutation in Phf6 display clinical features of Börjeson–Forssman–Lehmann Syndrome. Issue 7 (26th March 2021) - Ahmed, Raies; Sarwar, Shihab; Hu, Jinghua; Cardin, Valérie; Qiu, Lily R; Zapata, Gerardo; Vandeleur, Lucianne; Yan, Keqin; Lerch, Jason P; Corbett, Mark A; Gecz, Jozef; Picketts, David J
Abstract: The PHF6 mutation c.1024C > T; p.R342X, is a recurrent cause of Börjeson–Forssman–Lehmann Syndrome (BFLS), a neurodevelopmental disorder characterized by moderate–severe intellectual disability, truncal obesity, gynecomastia, hypogonadism, long tapering fingers and large ears (MIM#301900). Here, we generated transgenic mice with the identical substitution (R342X mice) using CRISPR technology. We show that the p.R342X mutation causes a reduction in PHF6 protein levels, in both human and mice, from nonsense-mediated decay and nonsense-associated alternative splicing, respectively. Magnetic resonance imaging studies indicated that R342X mice had a reduced brain volume on a mixed genetic background but developed hydrocephaly and a high incidence of postnatal death on a C57BL/6 background. Cortical development proceeded normally, while hippocampus and hypothalamus relative brain volumes were altered. A hypoplastic anterior pituitary was also observed that likely contributes to the small size of the R342X mice. Behavior testing demonstrated deficits in associative learning, spatial memory and an anxiolytic phenotype. Taken together, the R342X mice represent a good preclinical model of BFLS that will allow further dissection of PHF6 function and disease pathogenesis.